Predictive Ability as a Criterion for the Evaluation of Accounting Data. - Beaver, William H.; Kenndlly, John W.; Voss, William M. (The Accounting Review, 1968)
One criterion being employed by a growing body of empirical research is predictive ability. According to this criterion, alternative accounting measurements are evaluated in terms of their ability to predict events of interest to decision-makers. The measure with the greatest predictive power with respect to a given event is considered to be the best method for that particular purpose. Because the predictive ability criterion is currently being used and is likely to experience even greater use in the future, this article examines its origin, its relation-ship to the facilitation of decision-making, and the potential difficulties associated with its implementation. Knowing the origin of the predictive ability criterion is important in understanding what is meant by predictive ability and why it is being used in evaluating accounting data. The criterion is well established in the social and natural sciences as a method for choosing among competing hypotheses. The use of the predictive ability criterion presupposes that alternatives under consideration have met the tests of logic and that each has a theory supporting it.